Dampak Perkawinan Dibawah Tangan Terhadap Akses Pemenuhan Hak Anak - Eka Widiawati; Elfa Murdiana; Hud Leo Perkasa Maki (Al-Mizan (e-Journal), 2026)
Unregistered marriages remain prevalent in several rural areas in Indonesia, despite the implementation of mandatory marriage registration regulations. Previous studies have generally focused on the legal validity aspects of such marriages, while empirical research examining their impact on children’s access to rights at the local level remains limited. This study aims to fill this gap by analyzing the driving factors and impacts of unofficial marriages on the fulfillment of children’s rights in Wonosari Village, Mesuji Timur District, Mesuji Regency. This research is a field study employing a descriptive qualitative approach. Data were collected through in-depth interviews, direct observation, and document analysis involving couples in unofficial marriages, parents, community leaders, and local government officials. The findings reveal that economic vulnerability, premarital sexual activity, and environmental and family pressure are the primary factors driving the occurrence of unofficial marriages. Children born from such unions face significant obstacles in obtaining legal identity documents, accessing formal education, and securing adequate legal protection. This situation places both children and women in a socially and juridically vulnerable position. While these unofficial marriages are considered religiously valid, they lack legal force. This study provides an empirical contribution by presenting local evidence regarding the linkage between unofficial marriages and the fulfillment of children’s rights. Consequently, it underscores the importance of policy interventions, including simplifying marriage registration procedures, improving access to civil registration services, and strengthening collaboration among the government, religious institutions, and community stakeholders in protecting children’s rights.